Which Tools in Multimedia Are Best for Learning Outcomes? A Study Grounded in Cognitive Load Structures - Torgersen, Glenn-Egil; Boe, Ole (Frontiers in Psychology, 2021)
The main objective of this study is to investigate the importance of three compositions in multimedia for learning outcomes in relation to individual differences in short-term memory (STM) capacity. The study is based on a survey of 378 students at the bachelor level (military officers, teachers and psychology students). The learning outcomes of three different multimedia compositions (means) were tested. This applied to individuals with low, medium and high STM capacity. The results show that the successive presentation (Type II) of learning materials through multiple representation forms/channels (speech, pictures and screen text/labels) provides a better learning outcome than just speech (Type I) and simultaneous presentation (type III). Visual and verbal channel capacity overall did not contribute to the learning outcome in any of the three tools tested. But, some specific STM-capacity types or substructures (visual and verbal progressive capacity) and non-verbal (RAPM) types have significance, particularly for exploiting successive presentation (Type II) for learning. Although the tools used in multimedia educational material had a low cognitive load, the individuals with a low capacity learned relatively less than individuals with a higher capacity. A symbolic form of expression was introduced concerning the relationship between cognitive load structure (CLS) and learning outcomes (LO) through various tools in multimedia as an aid in our theoretical and empirical analyses. This is referred to as the CLS-LO formula. The study's main assumption, based on previous empirical and theoretical studies, is that the relationship between CLS and LO is expressed with CLS-LO formula: CLSType III > CLSType II > CLSType I LOType III > LOType I > LOType II Based on this study, the relationship became: CLSType III > CLSType I > CLSType II LOType II > LOType I = LOType III This basic research study is primarily a contribution to understanding underlying cognitive processes in the STM and their importance for learning in multimodal forms compared with analogue text. The findings will also be relevant as a basis for performance analysis and decision-making under high information pressure, risk and unpredictable conditions.